Reduced blood oxygenation level dependent connectivity is related to hypoperfusion in Alzheimer's disease. Issue 7 (July 2019) - Göttler, Jens; Preibisch, Christine; Riederer, Isabelle; Pasquini, Lorenzo; Alexopoulos, Panagiotis; Bohn, Karl Peter; Yakushev, Igor; Beller, Ebba; Kaczmarz, Stephan; Zimmer, Claus; Grimmer, Timo; Drzezga, Alexander; et al.
Functional connectivity of blood oxygenation level dependent signal fluctuations (BOLD-FC) is decreased in Alzheimer's disease (AD), and suggested to reflect reduced coherence in neural population activity; however, as both neuronal and vascular-hemodynamic processes underlie BOLD signals, impaired perfusion might also contribute to reduced BOLD-FC; 42 AD patients and 27 controls underwent simultaneous PET/MR imaging. Resting-state functional MRI assessed BOLD co-activity to quantify BOLD-FC, pulsed arterial spin labeling (pASL) assessed cerebral blood flow (CBF) as proxy for vascular hemodynamics, and 18 F-fluorodeoxyglucose PET assessed glucose metabolism (GluMet) to index neuronal activity. Patients' BOLD-FC, CBF, and GluMet were reduced within the same precuneal parietal regions. BOLD-FC was positively associated with mean CBF, specifically in patients and controlled for GluMet levels, suggesting that BOLD-FC reductions correlate with pASL-derived hypoperfusion in AD, independently from 18 F-fluorodeoxyglucose PET-derived hypometabolism. Data indicate that impaired vascular hemodynamic processes contribute to reduced BOLD connectivity in AD.